Green Synthesis of Iron Oxide Nanoparticles and its Application in Polluted Water Treatment - Mahdi, Zainab Saad; Hashim, Intesar H.; Jassim, Nadia M. (Iraqi Journal of Science, 2026)
The green synthesis of nanomaterials is of particular interest to researchers worldwide. It is described as a simple, robust, inexpensive, and environmentally friendly method. This research presented an easy and quick method to biosynthesize iron oxide nanoparticles (Fe3O4NPs) using hibiscus flower extract. The biosynthesized Fe3O4NPs were used to treat polluted water samples taken from different points on the Euphrates River in Iraq. The nanoparticles were characterized using X-ray diffraction (XRD), energy dispersive X-ray spectroscopy (EDX), field emission scanning electron microscopy (FE-SEM), atomic force microscopy (AFM), Fourier transform infrared spectroscopy (FTIR), the surface-enhanced Raman scattering (SERS) and ultraviolet-visible (UV-Vis) spectroscopy. The use of magnetic adsorbents, especially (Fe3O4) is a promising adsorbent for water purification due to its high surface area. Its superior magnetism and ease of operation make it suitable for absorbing many pollutants, as well as its biological effectiveness against gram-negative bacterial strains that are usually found in polluted water (Pseudomonas, Acinetobacter, Cholera, and Escherichia coli).